2020
DOI: 10.1111/bph.14980
|View full text |Cite
|
Sign up to set email alerts
|

HWL‐088, a new potent free fatty acid receptor 1 (FFAR1) agonist, improves glucolipid metabolism and acts additively with metformin in ob/ob diabetic mice

Abstract: Background and Purpose: The free fatty acid receptor 1 (FFAR1) plays an important role in glucose-stimulated insulin secretion making it an attractive antidiabetic target. This study characterizes the pharmacological profile of HWL-088(2-(2-fluoro-4-((2 0 -methyl-[1,1 0 -biphenyl]-3-yl)methoxy)phenoxy)acetic acid), a novel highly potent FFAR1 agonist in vitro and in vivo. Moreover, we investigated the longterm effects of HWL-088 alone and in combination with metformin in diabetic mice.Experimental Approach: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…[ 10,11 ] In previous studies, we found HWL‐088 exerted stronger hypoglycemic effect than TAK‐875, the most advanced candidate of FFA1 agonists. [ 29 ] However, the ability of HWL‐088 to protect NAFLD was unknown. Herein, we first evaluated the effects of PPARδ/FFA1 dual agonist in NASH model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10,11 ] In previous studies, we found HWL‐088 exerted stronger hypoglycemic effect than TAK‐875, the most advanced candidate of FFA1 agonists. [ 29 ] However, the ability of HWL‐088 to protect NAFLD was unknown. Herein, we first evaluated the effects of PPARδ/FFA1 dual agonist in NASH model.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25–28 ] A comprehensive structure‐activity relationship study provided HWL‐088 (the structure is shown in Figure 1a), a PPARδ/FFA1 dual agonist. [ 29,30 ] Herein, the chronic effects of HWL‐088 were explored in the methionine‐ and choline‐deficient diet (MCD) diet‐fed db/db mice, a typical model of NASH. [ 31 ] HWL‐088 alleviated fatty liver by maintaining glucose stability, improving fat metabolism, liver fibrosis, inflammation and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Another mechanism of FFA uptake is by binding to the free fatty acid receptor 1, also known as the G protein-coupled receptor (GPR) 40 [ 70 ]. GPR40 activates phospholipase C (PLC) [ 71 ] which is degrading phosphatidylinositol-4,5-bisphosphate into the signaling molecules inositol trisphosphate (IP3) and diacylglycerol to increase the cytosolic calcium (Ca) concentration [ 72 ]. Furthermore, Ca storages of the mitochondria are released by PLC, and the endoplasmic reticulum (ER) can release its Ca storages through the activation of GPR40 [ 71 ].…”
Section: Lipotoxic Action Of Ffa On Mitochondria In β-Cellsmentioning
confidence: 99%
“…The accumulation of especially long chain acyl-CoA in the cytosol induces functional impairment and apoptosis by mediating signaling effects and Ca release. Acyl-CoA interacts with PPARα [ 138 ] promoting apoptosis [ 72 ], uncoupling of respiratory complexes [ 133 ], and storage as TG [ 158 ], ultimately impairing GSIS [ 157 ]. Based on the acyl-CoA content of hamster islet transformed-tioguanine resistant clone 15 (HIT-T15) cells and the average distribution of cytosolic and mitochondrial mass in mouse pancreas [ 159 ], it is estimated that the cytosolic acyl-CoA concentration in rodent β-cells is 90 µM, while tissue concentrations are unknown [ 160 ].…”
Section: Lipotoxic Action Of Ffa On Mitochondria In β-Cellsmentioning
confidence: 99%
See 1 more Smart Citation